Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(e ) Để \) \(M\)\(\in\)\(Z \) \(thì\) \(1 \)\(⋮\)\(x +3\)
\(\Leftrightarrow\)\(x + 3 \)\(\in\)\(Ư\)\((1)\)\(= \) { \(\pm\)\(1 \) }
\(Lập\) \(bảng :\)
\(x +3\) | \(1\) | \(- 1\) |
\(x\) | \(-2\) | \(- 4\) |
\(Vậy : Để \) \(M\)\(\in\)\(Z\) \(thì\) \(x\)\(\in\){ \(- 4 ; - 2\) }
e) Để M \(\in\)Z <=> \(\frac{1}{x+3}\in Z\)
<=> 1 \(⋮\)x + 3 <=> x + 3 \(\in\)Ư(1) = {1; -1}
Lập bảng:
x + 3 | 1 | -1 |
x | -2 | -4 |
Vậy ....
f) Ta có: M > 0
=> \(\frac{1}{x+3}\) > 0
Do 1 > 0 => x + 3 > 0
=> x > -3
Vậy để M > 0 khi x > -3 ; x \(\ne\)3 và x \(\ne\)-3/2
Ta có : A=20+21+22+23+...+22010A=20+21+22+23+...+22010
3A=2+22+23+24+...+220113A=2+22+23+24+...+22011
=> 2A=3A−A=(21+22+...+22011)−(20+21+...+22010)
=>2A=22011−12A=22011−1
=>A=22011−12A=22011−12
=> A < B ( vì 22011−12<2201122011−12<22011 )
\(\left(\frac{1}{m}\right)^{\frac{9}{m}}=\left(\frac{1}{9}\right)^{\frac{9}{9}}=\frac{1}{9}\)
Vậy m = 9